The Concept of Bilingualism and Its Impact Towards Child Language Development - Ngadjen, Syahdania Aini; Patty, Jusak (MATAI: International Journal of Language Education, 2024)
This study aimed to show a deeper understanding of the world of bilingualism and its impact on child language development. In this study, the researcher used library research to explore the complexities of language acquisition, the various forms of bilingualism, and the stages of child language development. In short, bilingualism is crucial in shaping how children develop their language skills. Understanding these aspects is essential for addressing the linguistic and cultural implications of this fascinating aspect of human development. Future research in this field promises to offer more valuable insights into how bilingualism globally influences children's language development.